2005
DOI: 10.1016/j.amjhyper.2004.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Tempol Attenuates the Development of Hypertensive Renal Injury in Dahl Salt-Sensitive Rats

Abstract: Histopathologic and biochemical findings indicate that, in the DS rat, salt-induced hypertensive nephropathy is associated with increased oxidative stress. Superoxide mimetic tempol can reduce this detrimental effect of salt feeding through TGF-beta1 suppression and consequently prevent the development of hypertension and hypertensive nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 30 publications
2
41
0
Order By: Relevance
“…These studies, together with our present data, implicate T lymphocytes in the elevation of the oxidative state during hypertensive conditions. Treatment with the antioxidant tempol has been proven to decrease hypertension and renal damage in Dahl SS rats (18,26). In the present set of experiments, tempol treatment during the high-salt period ameliorated hypertension and albuminuria without affecting the infiltration of T cells into the kidney, which remained elevated.…”
Section: Discussionmentioning
confidence: 48%
“…These studies, together with our present data, implicate T lymphocytes in the elevation of the oxidative state during hypertensive conditions. Treatment with the antioxidant tempol has been proven to decrease hypertension and renal damage in Dahl SS rats (18,26). In the present set of experiments, tempol treatment during the high-salt period ameliorated hypertension and albuminuria without affecting the infiltration of T cells into the kidney, which remained elevated.…”
Section: Discussionmentioning
confidence: 48%
“…Tsukahara et al (2003) reported that high degree of oxidative stress in the renal tissue coincides with biochemical signs typical of DN, such as high levels of UAE and urinary proteins. Moreover, Hisaki et al (2005) demonstrated that a high salt intake increased urinary 8-OHdG excretion in a rat model of hypertension. Based on our results, urinary 8-OHdG excretion was significantly higher in WFR with high-salt dietinduced hypertension than in WFR fed a with normal-salt diet.…”
Section: Discussionmentioning
confidence: 97%
“…The antioxidant ␣-tocopherol prevents the development of hypertension and renal dysfunction in SS rats (7,28,96). The superoxide dismutase mimetic tempol reduces glomerular injury (43,63) and MAPK activity in Dahl SS rats (76). DHA attenuates the development of hypertension by decreasing NADPH oxidase activity in rats infused with ANG II (20).…”
Section: Discussionmentioning
confidence: 99%